Vibrational energy harvesting using smart materials - Teo, Edison Tze Chun. (2012)
This report depicts what the author had done in the whole academic year for vibrational energy harvesting using smart materials. During this time frame, the author and his partner carried out two experiments that each comprises of two parts. Firstly, the open circuit voltage (Voc) and short circuit current (Isc) is measured. Then, the peak power is obtained by connecting a variable resistor to the experimental setup. From the results of the first experiment, it is concluded that only 1 frequency produces the maximum Voc and Isc. Hence, it cannot be applied to practical situations as the exact frequency has to be determined first in real life situation. It can also be concluded that the peak power can be obtained when the internal impedance R = 100kΩ.